Ethnomathematics-based scaffolding: an innovation in classroom mathematics learning - Efrata Gee; Jarnawi Afgani Dahlan; Turmudi Turmudi (Jurnal Riset Pendidikan Matematika, 2026)
Difficulties in learning mathematics are commonly attributed to the gap between school mathematics and students’ lived experiences. Therefore, instruction should begin from contexts that are meaningful and familiar to students. Ethnomathematics, grounded in cultural practices, can serve as an alternative form of scaffolding to support students in overcoming learning difficulties. This study aims to examine the role of ethnomathematics as pedagogical scaffolding within students’ Zone of Proximal Development in geometry learning among eighth-grade students located in South Nias Regency, involving 28 participants. Using a qualitative descriptive approach, this study analysed classroom interactions, student interviews, and teacher reflections during instruction that integrated the stone-jumping tradition (Hombo Batu) as a context for learning truncated pyramids. Data were analysed thematically to explore how instructional support mediated students’ transition from informal understanding to formal geometric reasoning. The findings indicate a process-oriented learning pattern, in which cultural familiarity serves as an entry point that promotes student engagement. Guided questioning and visualisation function as key scaffolding mechanisms that facilitate conceptual bridging within the ZPD. As instructional support is gradually reduced, students demonstrate increased autonomy, supported by peer interaction. This process reflects gradual abstraction, suggesting that ethnomathematics can be understood as a mediational pathway in culturally responsive mathematics learning.